Practical sew & mend : essential mending know-how - Gordon, Joan, author (Lewes, East Sussex : Guild of Master Craftsman Publications Ltd, 2016)
A practical 'make do and mend' guide to help you fix your favorite pair of trousers. With basic sewing hints and tips, you can revive your existing wardrobe and save money at the same time! From sewing on a button to taking up a hem, everything is clearly explained so that even complete beginners can successfully tackle these tasks and more.
Text is stated as copyright date of 2009.
Includes index.
In English text.
Keywords: Clothing and dress -- Repairing; Household linens -- Repairing; Sewing; CRAFTS & HOBBIES -- Needlework